Gastric Stem Cells: Physiological and Pathological Perspectives - Xiao, Shiyu; Zhou, Liya (Frontiers in Cell and Developmental Biology, 2020)
Gastric epithelium operates in a hazardous environment that curtails the lifespan of the constituents cells, imposing a requirement for continuous epithelial renewal. Stems cells that reside in the stomach are thus essential for regulating physiological tissue renewal and injury repair because of their self-renewal, high proliferation capacity and multiple differentiation potentials. Recent investigations using lineage tracing models have identified diverse populations of gastric stem cells and even fully differentiated cells that can regain stem cell capacity, so enriching our understanding on the identity and plasticity of gastric stem cells. These cell populations include the Villin promotor, Lgr5+, CCKR2+, Axin2+ and AQP5+ stem cells in the antrum, TFF2 mRNA, Mist1+ cells and Troy+ mature chief cells in the corpus, as well as Sox2, eR1, Lrig1, Bmi1-marked cell in both the antrum and the corpus. Establishment of gastric organoids derived from primary gastric tissues and pluripotent stem cells or embryonic stem cells characterizes niche factors required by the gastric stem cell populations, and further provides new insights into stomach development, host-Helicobacter pylori interactions and malignant transformation. Furthermore, focus on the gastric stem cells and their niches uncovers the initiation of stomach precancerous lesions and origin of gastric cancer, providing options for cancer prevention and intervention. In summary, with the development of stem cell research, gastric stem cells give us more opportunities to prevent and treat stomach diseases.